(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Low molecular weight chitosan nanoparticles were prepared by ionotropic gelation of depolymerised chitosan for effective drug delivery in drug resistant bacteria. Depolymerisation reaction was performed by potassium persulfate oxidation at an optimized condition in presence of silver nitrate. Optimized condition for depolymerisation was anticipated at 37°C, pH 4, 2 days reaction time and 0.05 M concentration of potassium per sulphate with 1 mM silver nitrate in final reaction mixture. Chemical characteristics of depolymerised chitosan and low molecular weight chitosan nanoparticles were analyzed by gel permeation chromatography, nuclear magnetic resonance, scanning electron microscopy, X-ray diffraction, and transmission electron microscopy. Drug loading efficiency and drug releasing efficiency were also studied. Finally, antimicrobial activity of tetracycline loaded low molecular chitosan nanoparticles was determined in terms of minimal inhibitory concentration and putative mode of action on tetracycline resistant bacteria Escherichia coli XL-1 Blue.